New standards for the management of nose vestibule malignancies. (1st March 2023) - Bussu, Francesco; Tagliaferri, Luca; Crescio, Claudia; Rizzo, Davide; Gallus, Roberto; Parrilla, Claudio; Fionda, Bruno; Lancellotta, Valentina; Mattiucci, Gian Carlo; Galli, Jacopo
Abstract: Background: Nasal vestibule squamous cell carcinoma (NVSCC) is an ill-defined underestimated condition. Aim/objective: To define the current standard of care. Material and methods: We review recent acquisitions concerning clinical features and therapeutic approaches. Results: The current AJCC staging system, which attributes to nasal vestibule the same topographic code as nasal cavity proper and the same T-classification criteria as ethmoid, appears inadequate. As for treatment of primary lesions without bone invasion, current evidence suggests that brachytherapy is at least equivalent to surgery and superior to external beams in terms of oncological outcomes, and superior to both modalities in terms of cosmesis and function. Conclusions: As for classification and staging, the nasal vestibule should be defined as a subsite of the nose and paranasal sinuses, distinct from the 'nasal cavity proper and ethmoid', with specific topographic code and T-classification criteria. This will improve the assessment of prognosis and prevalence, underestimated also because of misdiagnosis with skin cancers. Secondly, brachytherapy should become the new standard for the treatment of primary lesions without bone invasion. To optimize the advantages of brachytherapy, we propose novel anatomic criteria for the implantation. Significance: Increasing evidence supports a paradigm shift in staging and treatment of NVSCC.